2021
DOI: 10.1002/jmv.27097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic role of NLR, LMR, PLR, and LCR ratio in COVID‐19 patients

Abstract: We aimed to find the most useful biomarker by examining the prognostic effect of neutrophil‐lymphocyte ratio (NLR), lymphocyte‐monocyte ratio (LMR), platelet‐lymphocyte ratio (PLR), and lymphocyte‐C reactive protein ratio (LCR) in patients with coronavirus disease 2019 (COVID‐19). Three hundred and four patients diagnosed with COVID‐19 infection in our hospital within 5 months (April–August 2020) were examined. Laboratory values and demographic findings of the patients were analyzed retrospectively. Thirty‐six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
7
45
0
6
Order By: Relevance
“…Unlike NLR, declined LMR was maintained at last day of hospitalization in patients with a fatal outcome compared to those who survived in ICU. In line with our finding, previous study revealed that decreased LMR value as an indicator of increased chances of mortality among patients suffering from COVID-19 disease in ICU [46] , [47] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Unlike NLR, declined LMR was maintained at last day of hospitalization in patients with a fatal outcome compared to those who survived in ICU. In line with our finding, previous study revealed that decreased LMR value as an indicator of increased chances of mortality among patients suffering from COVID-19 disease in ICU [46] , [47] .…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, it was observed in the current study that CLR in the deceased group remained high, while these values returned to normal more quickly in survivor’s patients. Similar results were documented in another study, which showed that the LCR is able to distinguish COVID-19 infected patients of different severity (mild/moderate, severe and critically ill) [47] , [48] . Erdogan A. et al [47] , [48] demonstrated that the LCR was significantly decreased in severe cases, suggesting that this marker could reflect the severity of COVID-19 disease.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There are a few reports regarding these scores pertaining to COVID-19 diagnosis. There are several other diagnostic scores for COVID-19, such as neutrophile-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio (22,24,26,(53)(54)(55)(56). Prior to the COVID-19 pandemic, these scores were used in the evaluation of malignant tumors (57,58).…”
Section: Prognostic Valuesmentioning
confidence: 99%